Peningkatan kemampuan menganalisis sumber energi melalui penerapan model Contextual Teaching and Learning dengan media Diorama pada kelas IV sekolah dasar - Slamet Tri Widodo; Sandra Bayu Kurniawan; Sukarno Sukarno (Universitas Sebelas Maret, 2019)
Abtract. The aim of this research are (1) to improve the ability of energy sources by implementing CTL with diorama; and (2) to describe of implementing CTL with diorama on students of class IV SD Negeri Triyagan 02 Sukoharjo in 2018/2019. The design of this research was a Classroom Action Research (CAR). The subject of this research were 28 students. The methods of data collection were documentary, observation, interview, and test. Those data were analyzed with two-ways (1) qualitative technique by using interactive model from Miles and Huberman; and (2) quantitative technique by using mean calculation in each cycle and categorization of the analytical ability based on normative referenced assessment. The result of this research showed there was an improvement mainly the ability of energy sources in second cycle. Pre-test, the classical completeness was only 10,7%. First cycle, the classical completeness had improved 46,42%. Second cycle, the classical completeness had significantly improved 82,14%. Based on the result of this research, it can be concluded that implementing Contextual Teaching and Learning Model with Diorama can improve the ability of energy sources on students of class IV SD Negeri Triyagan 02 Sukoharjo in 2018/2019.Keywords: Contextual Teaching and Learning Model, Diorama, The Ability of Energy Sources, Elementary School Students